2011
DOI: 10.1053/j.gastro.2011.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin Reduces Pancreatic Ductal Bicarbonate Secretion by Inhibiting CFTR Cl− Channels and Luminal Anion Exchangers

Abstract: Background & Aims The effects of trypsin on pancreatic ductal epithelial cells (PDEC) vary among species and depend on localization of proteinase-activated receptor-2 (PAR-2). Bicarbonate secretion is similar in human and guinea pig PDEC; we compared its localization in these cell types and isolated guinea pig ducts to study the effects of trypsin and a PAR-2 agonist on this process. Methods PAR-2 localization was analyzed by immunohistochemistry in guinea pig and human pancreatic tissue samples (from 15 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 50 publications
2
84
0
Order By: Relevance
“…Although the toxic effects of ethanol and POA were similar to those of a high concentration of bile acids, 27,28 in this study chelation of [Ca 2+ ] i abolished the inhibitory effect of ethanol and POA on HCO 3 − secretion. This observation indicates that ethanol and POA, in a similar manner to trypsin, 29 inhibit HCO 3 − secretion via a sustained increase in [Ca 2+ ] i . Importantly, CFTR single channel parameters do not change as a result of use of ethanol (personal communication, Aleksandrov Andrei and John R. Riordan), suggesting that the effects of a high dose of ethanol do not alter the biophysical characteristics of CFTR.…”
Section: Discussionmentioning
confidence: 75%
“…Although the toxic effects of ethanol and POA were similar to those of a high concentration of bile acids, 27,28 in this study chelation of [Ca 2+ ] i abolished the inhibitory effect of ethanol and POA on HCO 3 − secretion. This observation indicates that ethanol and POA, in a similar manner to trypsin, 29 inhibit HCO 3 − secretion via a sustained increase in [Ca 2+ ] i . Importantly, CFTR single channel parameters do not change as a result of use of ethanol (personal communication, Aleksandrov Andrei and John R. Riordan), suggesting that the effects of a high dose of ethanol do not alter the biophysical characteristics of CFTR.…”
Section: Discussionmentioning
confidence: 75%
“…Overexpression of trypsin(ogen), including but not restricted to hereditary pancreatitis-relevant mutant trypsinogen isoforms, leads to pancreatic injury or more severe pancreatitis (37,50), but the deletion of other trypsinogen isoforms does not have the expected opposite effect of reducing disease severity (27). Although our experiments do not exclude CTSB effects in nonacinar cells or extrapancreatic effects of CTSB-induced trypsin activation (38), our data regarding the role of CTSB activation inside the vesicular compartment of acinar cells are quite unequivocal. CTSB activation induces apoptosis rather than necrosis of acinar cells in a pancreas-specific mechanism.…”
Section: Figurementioning
confidence: 80%
“…Recent experimental studies in rodents have suggested that the role of trypsin is probably more complex than just being a triggering event when the enzyme is activated or that of a disease driver when its activity persists. They found that activation and inhibition of trypsin does not necessarily affect the acute, recurrent, and chronic phase of the disease in the same manner (26,37) and even suggested that some injurious effects of trypsin may be extra-rather than intracellular (38).…”
Section: Figurementioning
confidence: 99%
“…The presence of active trypsin in the pancreatic duct lumen may lead to additional reduction in bicarbonate secretion due to inhibition of CFTR and other luminal anion exchangers (e.g. SLC26) via proteinase-activated receptor 2 [24]. Further reduction in bicarbonate secretion by the ductal epithelium generates a vicious cycle and environment of falling pH, enhanced trypsinogen activation and decreased intraluminal fluid volume, which promotes the development of pancreatitis.…”
Section: Pathogenesismentioning
confidence: 99%